When all seems lost: management of refractory constipation—Surgery, rectal irrigation, percutaneous endoscopic colostomy, and more. Issue 5 (26th April 2018) - Wilkinson‐Smith, V.; Bharucha, A. E.; Emmanuel, A.; Knowles, C.; Yiannakou, Y.; Corsetti, M.
Abstract: While the pharmacological armamentarium for chronic constipation has expanded over the past few years, a substantial proportion of constipated patients do not respond to these medications. This review summarizes the pharmacological and behavioral options for managing constipation and details the management of refractory constipation. Refractory constipation is defined as an inadequate improvement in constipation symptoms evaluated with an objective scale despite adequate therapy (ie, pharmacological and/or behavioral) that is based on the underlying pathophysiology of constipation. Minimally invasive (ie, rectal irrigation and percutaneous endoscopic colostomy) and surgical therapies are used to manage refractory constipation. This review appraises these options, and in particular, percutaneous endoscopic colostomy, which as detailed by an article in this issue, is a less invasive option for managing refractory constipation than surgery. While these options benefit some patients, the evidence of the risk: benefit profile for these therapies is limited.